NEW FAUNAL DATA ON TRUE BUGS (HETEROPTERA) IN SERBIA (Acta Entomologica Serbica, 2019)
Three new true bugs were recorded in Serbia and species are listed with notes on records. Anisops sardeus Herrich-Schäffer, 1849; Henestaris laticeps (Curtis, 1836); Caenocoris nerii (Germar, 1847).